Inhibition by D-MePhe-Pro-Arg-H (GYKI-14766) of Thrombus Growth in Experimental Models of Thrombosis - Bagdy, Dániel; Szabó, Gabriella; Barabás, Éva; Bajusz, Sándor (Thrombosis and Haemostasis, 1992)
The antithrombotic action of the highly effective synthetic thrombin inhibitor D-MePhe-Pro-Arg-H (GYKI-14766) was studied in various models of experimental thrombosis. The compound administered to rats and rabbits by i. v. bolus injections, continuous i. v. infusions, subcutaneously and orally, respectively, induced significant decrease in thrombus weight (i) in a quantitative venous thrombosis model with stasis based on vascular lesion in rats, (ii) in an extracorporeal arterio-venous shunt model in rabbits, and (iii) prevented the occlusion of the vessel in arterial thrombosis induced by mechanical damage in rats. By using the arterio-venous shunt model in rabbits the inhibitory effect on thrombus growth could be demonstrated as a function of dose and time in self-controlled experiments. Blood level of the inhibitor determined by a bioassay varied between 0.09-0.67 µg/ml whole blood when doses of 15 and 20 mg/kg were administered orally. A correlation was found between thrombin time, platelet aggregation induced by thrombin ex vivo and the weight of thrombi formed.